2022
DOI: 10.1007/s12144-022-03389-0
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 anxiety, psychological well-being and preventive behaviors during the COVID-19 pandemic in Latin America and the Caribbean: relationships and explanatory model

Abstract: This study assesses the relationship between COVID-19 anxiety and subjective well-being in terms of the mediating role of COVID-19 preventive behaviors. Additionally, the contribution of sociodemographic factors (sex and age) and risk perception on COVID-19 anxiety and its potential measurement invariance was tested in 5655 participants from 12 countries in Latin America and the Caribbean. A mixture of both latent and observable variables were analyzed using a system of structural equations. The Coronavirus An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 109 publications
1
3
0
Order By: Relevance
“…However, harm avoidance moderates the relationship between fear of COVID-19 and obsessivecompulsive behavior non-significantly. The findings of current study are supported by Rodríguez et al, (2022) study carried out on variables of COVID-19 anxiety, psychological well-being and preventative behavior on a sample of 5655 Americas and Caribbeans. The results showed that COVID-19 anxiety has a direct and significant effect on individual's wellbeing.…”
Section: Discussionsupporting
confidence: 78%
“…However, harm avoidance moderates the relationship between fear of COVID-19 and obsessivecompulsive behavior non-significantly. The findings of current study are supported by Rodríguez et al, (2022) study carried out on variables of COVID-19 anxiety, psychological well-being and preventative behavior on a sample of 5655 Americas and Caribbeans. The results showed that COVID-19 anxiety has a direct and significant effect on individual's wellbeing.…”
Section: Discussionsupporting
confidence: 78%
“…The abstinent group clustered with the oldest average age, highest proportion of female members and a greater prevalence of at-risk conditions: these demographic covariates have been variably associated with the employment of protective behaviours to an excessive degree in other datasets (Cao, Siu, Shek, & Shum, 2022;Caycho-Rodríguez et al, 2022;Miola et al, 2023;Ye et al, 2020). This cluster also demonstrated the highest rates of certain health behaviours, with more than half shopping exclusively online due to COVID fears, and the greatest rates of never leaving home and disinfecting all items coming in to their homes.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 98%
“…In Iran as COVID-19 anxiety increased, cybercronymy behavior, which is the emotional distress experienced as a result of repetitive search for health-related information, increased in the general sample (Wu et al 2021). In the general sample of 300 participants from each of the Latin American and Caribbean countries, increased anxiety changed consumer behavior and predicted impulsive and compulsive buying behavior, which negatively affected the well-being of individuals (Caycho Rodríguez et al 2022).…”
Section: Relationship Between Covid-19 Anxiety and Psychological Healthmentioning
confidence: 99%
“…However, this pandemic has significantly negatively affected the psychological well-being of individuals in the worldwide (Erdoğdu et al 2020, Sani et al 2020. It has drawn attention that one of the most important predictors affecting the psychological well-being of individuals during and even after the COVID-19 pandemic is COVID-19 anxiety (Lee et al 2020, Banerjee et al 2022, Caycho Rodríguez et al 2022.…”
Section: Introductionmentioning
confidence: 99%